Clinical response to therapy with thymopoietin pentapeptide (TP-5) in rheumatoid arthritis. Issue 5 (October 1982) - Veys, E. M.; Huskisson, E. C.; Rosenthal, M.; Vischer, T. L.; Mielants, H.; Thrower, P. A.; Scott, J.; Ott, H.; Scheijgrond, H.; Symoens, J.
Abstract : The effect of thymopoietin pentapeptide (TP-5) was evaluated in patients with rheumatoid arthritis (RA). Ninety-two patients were divided into 3 groups, namely, placebo, TP-5 intramuscularly (IM) 1 mg, TP-5 intravenously (IV) 50 mg, and were evaluated for 6 measures of disease activity at the beginning of the study and at 3 and 6 months. No difference was observed between the placebo group and the group treated with TP-5 IM 1 mg. However, in the group treated with TP-5 IV 50 mg a statistically significant improvement of all parameters except the ESR was observed.